STRATEGI KOMUNIKASI PEMASARAN KAKAKU COFFEE SHOP MELALUI MEDIA SOSIAL INSTAGRAM DALAM MENJAGA HUBUNGAN BAIK DENGAN PELANGGAN - Reza Fachrezi; Silvina Mayasari; Sari Ekowati (CV Edujavare Publishing, 2025)
This study is based on the growing role of social media, particularly Instagram, in the marketing communication strategies of coffee shops. The research fills a gap in the understanding of digital relationship marketing in MSME (UMKM) contexts, which remains underexplored. This qualitative descriptive study employs interviews and observations with the owner and social media specialist of Kakaku Coffee. Findings reveal that Kakaku Coffee uses Instagram strategically through interactive content, features like Reels, Stories, and Feed, as well as monthly events such as “Kakacult”. Although Meta Ads are used with a limited budget, organic strategies prove more effective in fostering customer engagement. The discussion highlights how warm communication, consistent visuals, and customer involvement through reposts and comments significantly contribute to brand loyalty. The study concludes that Instagram is an effective tool for building long-term relationships with customers. It is recommended that Kakaku Coffee expand CSR programs, optimize TikTok, and establish a clearer customer feedback system.